Propriedades ópticas e magneto-ópticas de heteroestruturas WSe2/ β-Ga2O3 - Cavalini, Camila (Universidade Federal de São Carlos, 2024)
Transition metal dichalcogenides (TMDs) have been the subject of intense study in recent years due to their unique properties. In their three-dimensional configuration (3D), they are known as indirect bandgap semiconductors, but when reduced to a single layer (monolayer), they become direct bandgap materials. On the other hand, monoclinic gallium oxide (β-Ga2O3) has sparked great interest due to its remarkable characteristics: a wide bandgap ranging from 4.6 to 4.9 eV, high electron mobility exceeding 200 cm²/Vs, and high resistance to electric fields reaching approximately 8 MV/cm. Although it does not possess a van der Waals structure like TMDs, its crystalline organization enables exfoliation and association with two-dimensional (2D) materials. This study focuses on investigating the optical and magneto-optical properties of a monolayer of molybdenum diselenide (WSe2), a TMD, deposited on flakes and bulk crystals of β-Ga2O3, under the influence of perpendicular magnetic fields up to 9T. In addition to obtaining high-quality samples that maintained notable temporal stability, we identified several distinct emission peaks associated with the presence of localized excitons due to defects in the band structure. We conducted a detailed analysis of photoluminescence at room temperature and low temperatures, as well as magneto-photoluminescence, including the determination of the g-factors of the identified peaks. The results revealed the presence of different defects influencing the localization of excitons in WSe2. Our studies indicate that β-Ga2O3 is a promising dielectric material for two-dimensional (2D) materials, capable of opening new perspectives in the exploration of fundamental physics principles, with potential applications in optoelectronics and quantum information technologies.
Optical and magneto-optical properties of WSe2/ β-Ga2O3 heterostructures
Keywords: TMDs; Semicondutores; Óxido de gálio monoclínico; β-Ga2O3; Materiais bidimensionais; WSe2; Propriedades ópticas; Disseleneto de tungstênio; PL; Magneto-fotoluminescência; Fotoluminescência; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::PROP.OTICAS E ESPECTROSC.DA MAT.CONDENS;OUTRAS INTER.DA MAT.COM RAD.E PART.